Childhood Trauma in Patients With PAH—Prevalence, Impact on QoL, and Mental Health—A Preliminary Report - Park, Da-Hee; Meltendorf, Tanja; Kahl, Kai G.; Kamp, Jan C.; Richter, Manuel J.; Gall, Henning; Ghofrani, Hossein A.; Hoeper, Marius M.; Olsson, Karen M.; Fuge, Jan (Frontiers in Psychiatry, 2022)
Background/Objective: Child maltreatment is associated with increased risk of psychological consequences, contributes to morbidity and has long lasting effects on mental health and quality of life. Child maltreatment has not been assessed in patients with pulmonary arterial hypertension (PAH). We examined the prevalence of child maltreatment and determined their impact on disease severity in patients with PAH. Methods: A cross-sectional observational multicenter study at two PH centers in Germany was conducted. Patients with a confirmed diagnosis of PAH were given a self-administered questionnaire. Child maltreatment using the Childhood Trauma Questionnaire (CTQ), quality of life (QoL), anxiety, depression and lifestyle factors were assessed and enhanced by clinical parameters 6-minute walk distance (6MWD), WHO functional class (WHO FC), and serum levels of N-terminal fragment of pro-brain natriuretic peptide (NT-proBNP). Prevalence rates of child maltreatment were compared to the general population and impact of child maltreatment on disease severity was calculated by logistic regression analysis. Results: 217 patients, 71% female and a median age of 56 years were enrolled in this study. Patients with PAH had higher rates of emotional abuse and lower rates of physical neglect compared to the German population while rates of emotional neglect, physical abuse and sexual abuse did not differ between patients and German population. Patients with any form of child maltreatment were more likely to be active smokers, had a worse QoL and more anxiety or depression. Moderate associations between child maltreatment, mental health, QoL, lifestyle factors and clinical parameters could be observed. Logistic regression analysis showed a significant impact of CTQ-total score on disease severity with an OR of 1.022 (95%-CI 1.001-1.042, p=0.035). Conclusion: We found a higher rate of child maltreatment in patients with PAH in comparison to the German population. Correlations suggest moderate associations between CTQ-scores and mental health as well as QoL. Child maltreatment had significant impact on disease severity. However, effects were moderate. We conclude that child maltreatment has effects on mental health and quality of life in patients with PAH and may have limited effect on disease severity.